Rotational dynamics of the imidazolium ion in cyanide-bridged dielectric framework materials. Issue 79 (4th September 2020) - Phillips, Anthony E.; Cai, Guanqun; Demmel, Franz
Abstract : Quasielastic neutron scattering reveals the geometry and timescale of the dielectric switching dynamics in a series of elpasolite-like framework materials. Abstract : Reorientation of organic cations in the cubic interstices of cyanoelpasolite molecular perovskites results in a variety of structural phase transitions, but far less is known about these cations' dynamics. We report quasielastic neutron scattering from the materials (C3 H5 N2 )2 K[M III (CN)6 ], M = Fe, Co, which is directly sensitive to the rotation of the imidazolium ion. The motion is well described by a circular three-site hopping model, with the ion rotating within its plane in the intermediate-temperature phase, but tilting permanently in the high-temperature phase. Thus the two rhombohedral phases, which are crystallographically rather similar, have markedly different dynamics. The activation energy of rotation is about 10 kJ mol −1 and the barrier between orientations is 6 kJ mol −1 . Our results explain two anomalous features in these materials' dielectric constants.